ON CURVES IN THE LIGHTLIKE CONE - Oztekin, Handan Balgetir; Ergut, Mahmut (Inst Applied Mathematics, 2011)
In this paper we define support function for curves with constant cone curvature K in the 2-dimensional lightlike cone and the evolute-involute curves and then characterize curves which satisfy eigenvalue equations for the support function in relation to the evolute-involute curves.
Keywords: lightlike cone; involute; evolute; eigenvalue equation